Efficient hydrogenation of organic carbonates, carbamates, and formates indicates alternative routes to methanol based on CO2 and CO - Balaraman, Ekambaram; Gunanathan, Chidambaram; Zhang, Jing; Shimon, Linda J. W.; Milstein, David (Nature Chemistry, 2011)
Catalytic hydrogenation of organic carbonates, carbamates and formates is of significant interest both conceptually and practically, because these compounds can be produced from CO2 and CO, and their mild hydrogenation can provide alternative, mild approaches to the indirect hydrogenation of CO2 and CO to methanol, an important fuel and synthetic building block. Here, we report for the first time catalytic hydrogenation of organic carbonates to alcohols, and carbamates to alcohols and amines. Unprecedented homogeneously catalysed hydrogenation of organic formates to methanol has also been accomplished. The reactions are efficiently catalysed by dearomatized PNN Ru(II) pincer complexes derived from pyridine- and bipyridine-based tridentate ligands. These atom-economical reactions proceed under neutral, homogeneous conditions, at mild temperatures and under mild hydrogen pressures, and can operate in the absence of solvent with no generation of waste, representing the ultimate ‘green’ reactions. A possible mechanism involves metal–ligand cooperation by aromatization–dearomatization of the heteroaromatic pincer core.

Electron-rich PNP- and PNN-type Ru(II) hydrido-borohydride complexes. synthesis, structure and catalytic activity towards dehydrogenation of alcohols and hydrogenation of esters - Zhang, Jing; Balaraman, Ekambaram; Leitus, Gregory; Milstein, David (Organometallics, 2011)
Electron-rich PNP- and PNN-type ruthenium(II) hydrido borohydride pincer complexes, [RuH(BH4)(tBu-PNP)] (tBu-PNP = (2,6-bis(di-tert-butylphosphinomethyl)pyridine) (5) and [RuH(BH4)(tBu-PNN)] (tBu-PNN = 2-di-tert-butylphosphinomethyl-6-diethylaminomethylpyridine) (6), were prepared from their corresponding N2-bridged dinuclear Ru(II) complexes [(tBu-PNP)RuCl2]2(μ-N2) (3) and [(tBu-PNN)RuCl2]2(μ-N2) (4), respectively. The X-ray structure of 5 reveals a BH4– anion η2 coordinated to ruthenium through two bridging hydrides. A variable-temperature 1H NMR study of 6 exhibits interesting fluxional behavior of the BH4– ligand. Similarly, the Ru(II) hydrido borohydride complex 9, in which the BH4– moiety is coordinated in a η1 bonding mode, was obtained by reaction of [RuCl2(PPh3)(iPr-PNP)] (iPr-PNP = 2,6-bis(diisopropylphosphinomethyl)pyridine) (8) with two equivalents of NaBH4 at room temperature. The hydrido borohydride pincer complexes 5, 6, and 9 catalyze the acceptorless dehydrogenative coupling of primary alcohols to esters and the dehydrogenation of secondary alcohols to the corresponding ketones, accompanied by evolution of hydrogen gas. The reactivity follows the order 6 > 9 > 5. With the hydrido borohydride complex 6 as catalyst, high yields (up to 98%) and high turnover numbers (TON ∼1000) were obtained in the dehydrogenation of primary alcohols under mild and neutral conditions. In addition, 6 effectively catalyzes the hydrogenation of nonactivated aromatic and aliphatic esters to the corresponding alcohols with TON ∼200 under a relatively mild pressure of dihydrogen and neutral and homogeneous conditions. Thus, an efficient homogeneous catalytic system for the dehydrogenation–hydrogenation reactions of alcohols is developed, which is relevant to the current interest in hydrogen storage.

Efficient hydrogenation of biomass derived cyclic di-esters to 1,2-diols - Balaraman, Ekambaram; Fogler, Eran; Milstein, David (Chemical Communications, 2012)
The unprecedented homogeneous hydrogenation of cyclic di-esters, in particular biomass-derived glycolide and lactide, to the corresponding 1,2-diols is catalyzed by Ru(II) PNN (1) and Ru(II) CNN (2) pincer complexes under mild hydrogen pressure and (in the case of 1) neutral conditions. No racemization was observed when a chiral di-ester was used.

Expedient cobalt-catalyzed C–H alkynylation of (enantiopure) benzylamines - Landge, Vinod Gokulkrishna; Midya, Siba Prasad; Rana, Jagannath; Shinde, Dinesh R.; Balaraman, Ekambaram (Organic Letters, 2016)
A unified strategy for cobalt-catalyzed ortho-C-H bond alkynylation of benzylamines is reported. Simple, commercially available CoBr2 was used as a cobalt source. The developed alkynylation strategy is robust and efficient and has a broad substrate scope including 1 degrees, 2 degrees, and 3 degrees benzylamines. The mechanistic study shows that C-H bond cleavage is reversible, and the kinetic study illustrates that the rate of reaction depends solely on the catalyst.
Keywords: Terminal Alkynes; Bond Activation; Directed Functionalization; Aminoquinoline Benzamides; Ortho-C(Sp(2))-H Bonds; Mechanistic Insights; Selective Access; Carbon-Hydrogen; Nickel; Annulation

Efficient solar light-driven H-2 production: post-synthetic encapsulation of a Cu2O co-catalyst in a metal-organic framework (MOF) for boosting the effective charge carrier separation - Karthik, Peramaiah; Balaraman, Ekambaram; Neppolian, Bernaurdshaw (Catalysis Science & Technology, 2018)
The development of new and efficient catalytic systems for solar light-driven hydrogen generation is one of the prime focuses of contemporary chemical sciences. Indeed, the charge carrier separation efficiency of a photocatalyst plays a vital role in photocatalysis. Herein, we have successfully designed a Cu2O-encapsulating NH2-MIL-125(Ti) MOF by a post-synthetic encapsulation strategy. The Cu2O-encapsulating MOF material showed a remarkable enhancement in photocatalytic H-2 production activity under solar light illumination. Gratifyingly, the H-2 production activity under solar light was around approximate to 28-fold higher than that of the pristine MOF. The enhancement in photocatalytic activity may be attributed to efficient charge carrier separation through Ti3+ sites and the broad light absorption of the Cu2O-encapsulating MOF photocatalyst. The possible electron transport mechanism, potential energy diagram (V vs. NHE), and the existence of Ti3+ ions have been demonstrated by various spectroscopic studies.